Dental caries and endemic dental fluorosis in rural communities, Minas Gerais, Brazil - Simone de Melo Costa; Mauro Henrique Nogueira Guimarães Abreu; Andréa Maria Duarte Vargas; Mara Vasconcelos; Efigênia Ferreira e Ferreira; Lia Silva de Castilho (Revista Brasileira de Epidemiologia, 2013)
It is observational, analytical and cross-sectional aimed to evaluate the association between severity and prevalence of fluorosis and dental caries in rural communities with endemic dental fluorosis in the north state of Minas Gerais, Brazil, with fluoride concentrations in water up to 4.8 mg/L. Data were collected by one examiner (intra-examiner kappa, 0.96 to 0,95 for caries and fluorosis) after toothbrushing. The study included 511 individuals aged 7 - 22 years, categorized according to age: 7 - 9 years (n = 227), 10 to 12 years (n = 153), 13 to 15 years (n = 92), 16 to 22 years (n = 39). For the diagnosis of dental caries used the criteria of the World Health Organization to measure indices DMFT. For fluorosis used the index Thylstrup and Fejerskov (TF), dichotomized according to prevalence (TF = 0 and TF > 0) and severity (TF < 4 and TF > 5). In the two younger groups, the DMFT and its decay component were higher in the group with more severe fluorosis (p < 0.001). This association was not found among adolescents and adults (p > 0.05). The association was found between the conditions more severe fluorosis and caries in individuals under 12 years.